Magnetron High Voltage System Eight Cavity Stability Analysis Under Parameters Variation - Aluf, Ofer (Discoveries in Agriculture and Food Sciences, 2016)
A magnetron is a high power microwave oscillator in which the potential energy of an electron cloud near the cathode is converted into RF energy in a series of cavity resonators. As depicted by the low frequency analog, the rear wall of the structure may be considered the inductive portion, and the vane tip region the capacitor portion of the equivalent resonant circuit. The resonance frequency of a microwave cavity is thereby determined by the physical dimension of the resonator together with the reactive effect of any perturbations to the inductive or capacitive portion of the equivalent circuit. In order to sustain oscillations in a resonant circuit, it is necessary to continuously input energy in the correct phase. An eight cavity magnetron is the typical magnetron we analyze with discussion of stability. For an eight-resonator magnetron, the important modes are n = 1; 2; 3; 4. In general n = 1; 2; 3:::N=2 where N is the number of resonators or cavity. The equivalent circuit of a chain of LC elements may be considered in a planar circuit using split-ring resonators to realize each LC. The open space between the magnetron’s cathode and anode is called interaction space, where E and B fields interact with electrons—these are accelerated and emit radiation at a frequency determined by the cavity dimensions. The eight cavity magnetron equivalent circuit can be analyzed for stability behavior under different parameter variations. There is a practical guideline that combines graphical information with analytical work to effectively study the local stability of models. The stability of a given steady state is determined by phase space plot of a number of magnetron parameters.